Homeschooling and the Redefinition of Citizenship - Arai, A. Bruce (Education Policy Analysis Archives, 1999)
Homeschooling has grown considerably in many countries over the past two or three decades. To date, most research has focused either on comparisons between schooled and homeschooled children, or on finding out why parents choose to educate their children at home. There has been little consideration of the importance of homeschooling for the more general issue of citizenship, and whether people can be good citizens without going to school. This paper reviews the research on homeschooling, as well as the major objections to it, and frames these debates within the broader issues of citizenship and citizenship education. The paper shows that homeschoolers are carving out a different but equally valid understanding of citizenship and that policies which encourage a diversity of understandings of good citizenship should form the basis citizenship education both for schools and homeschoolers.